What Is the Empirical Research Base of Early Childhood Coaching? A Mapping Review - Schachter, Rachel E.; Goldberg, Molly J.; Knoche, Lisa L.; Lu, Junrong (Review of Educational Research, 2024)
This study examined the empirical base for early childhood (birth to 8) coaching via a systematic mapping review of the relevant literature, including diverse research designs to represent the full breadth of published studies related to early childhood coaching. The systematic review yielded 374 unique studies published between 1987 and 2019 that were coded for type of study design (e.g., causal; quantitative noncausal; qualitative; single-case design); research populations; and reported content, structure, and processes of early childhood coaching. Descriptive analyses revealed that almost half of the study designs were causal (45.99%); over 75% of the studies were interested in the outcomes or experiences of teachers. The most targeted coaching content domains were social-emotional (44.92% of studies) and language/literacy development (43.58% of studies). Reporting on coaching structure was inconsistent across studies. Observation was the most reported coaching strategy during instruction (73.53% of studies), and provision of evaluative feedback was the most frequently reported coaching strategy outside of instruction (62.83% of studies). The review identified the literature base includes a diversity of study designs, and a great majority of studies occur in preschool settings (70.32%). Findings also suggest that a growing number of coaching studies are focused on child outcomes (60.16%). Results indicate a need for more studies that focus on coaches directly as well as research about coaching in infant/toddler programs and in content domains beyond social-emotional and language/literacy.
Keywords: Adult Learners; Coaching; Professional Learning; Systematic Mapping Review; Early Childhood